Some complexes of N-aryl furfural nitrones with Co (II), Ni (II), Cu (II), Zn (II) and Cd (II) chlorides - Taqa, Amer A. (International Journal of Advanced Chemistry, 2016)
Some new metal(II) dichloride complexes with the ligands substituted nitrones of the general formula [ML2Cl2], where M= Co(II), Ni(II), Cu(II), Zn(II) and Cd(II), L=OCH=CHCH=C-CH=N(O)C6H4X (X=H,p-CH3,CH3O,CH3CO,F,Cl,and Br) have been prepared and characterized by elemental analysis, IR,1H,13C NMR and Vis/Uv spectroscopy. The IR spectral data showed that the nitrone ligands coordinated with the metal ion through the most active atom of the N-oxide to give square planner coordinate (Cu,Ni,) complexes and (Zn,Cd,Co) tetrahedral complexes. No correlation was observed between the N-O vibrations stretching high frequency Î½ (N-O) of the complexes and the Hammet (Ïƒ) constants.